VD_FINDINFO Jug / 2016 / 313 vom 26. August 2016 - VD Tribunal cantonal (2016)
DÉPENS, RÉDUCTIONEN GÉNÉRAL, CONTRAVENTION, FIXATION DE L'AMENDE, TRIBUNAL FÉDÉRAL | 107 LTF, 398 al. 1 CPP (CH), 429 CPP (CH)